2012
DOI: 10.1371/journal.pone.0034978
|View full text |Cite
|
Sign up to set email alerts
|

Complement C1 Esterase Inhibitor Levels Linked to Infections and Contaminated Heparin-Associated Adverse Events

Abstract: Activation of kinin-kallikrein and complement pathways by oversulfated-chondroitin-sulfate (OSCS) has been linked with recent heparin-associated adverse clinical events. Given the fact that the majority of patients who received contaminated heparin did not experience an adverse event, it is of particular importance to determine the circumstances that increase the risk of a clinical reaction. In this study, we demonstrated by both the addition and affinity depletion of C1inh from normal human plasma, that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It has been noted that adverse reactions to OSCScontaminated heparin are inversely correlated with C1inh plasma levels (Zhou et al, 2012a). On one hand, OSCS appears to activate the contact system through prekallikrein activation; on the other hand, OCSC seems to inhibit the contact system through potentiation of C1inh.…”
Section: Other Heparin-activated Serpinsmentioning
confidence: 99%
“…It has been noted that adverse reactions to OSCScontaminated heparin are inversely correlated with C1inh plasma levels (Zhou et al, 2012a). On one hand, OSCS appears to activate the contact system through prekallikrein activation; on the other hand, OCSC seems to inhibit the contact system through potentiation of C1inh.…”
Section: Other Heparin-activated Serpinsmentioning
confidence: 99%
“…Oversulfated chondroitin sulfate (OSCS), a contaminant in heparin linked to the 2008 heparin adverse events in the United States, has become the subject of multidisciplinary investigations [1] , [2] . Initially, OSCS was found to cause the activation of contact system (also known as the intrinsic pathway of coagulation or kallikrein/kinin system [3] ) through binding with factor XII and generation of plasma kallikrein and bradykinin, as well as the anaphylatoxins C3a and C5a [4] , [5] . OSCS also interacts with other parts of the innate immune system including most of the elements in the classical complement pathway [6] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of patients who received contaminated heparin did not experience an adverse event. To clarify this fact, a study was performed including the analysis of patient data and plasma samples [65]. It revealed that low C1-INH levels turned out as a risk factor for adverse events, whereas high levels were suggested to be protective, which once again emphasizes the importance of an appropriate C1-INH function.…”
Section: Discussionmentioning
confidence: 99%